Natural plants of the Sandras Mountain (Köyceğiz-Muğla) traditionally employed for therapeutic purposes - Serhat Davran; Merve Çıtakoğlu; Kenan Akbaş (Turkish Journal of Forestry, 2024)
This study was carried out between 2022 and 2023 in Yayla, Çayhisar, Sazak and Otmanlar neighborhoods located at the foothills of Sanras Mountain (Köyceğiz-Muğla). The main material of the study consists of plants determined as a result of surveys conducted with people living in these neighborhoods. A total of 73 people were interviewed in the survey. 41 of them are men and 32 are women. As a result of the interviews, it was determined that the local people benefit from 46 plant taxa growing naturally in the environment for therapeutic purposes. Among all plants evaluated; Salvia fruticosa Mill. and Origanum onites L. are seen as the most preferred by the local people. They use these plants through infusion in village coffeehouses and homes.